Investigation of aquaculture dynamics at a Ramsar site, using earth observation systems in conjunction with a socio-economic assessment - Nagabhatla, Nidhi; Pattnaik, C.; Senaratna Sellamuttu, Sonali; Prasad, N.; Wickramasuriya, R.; Finlayson, C. Max (Wiley, 2009)
This study presents a comprehensive site-scale analysis conducted within the global wetland inventory and mapping (GWIM) project. GWIM was developed and promoted by the International Water Management Institute (IWMI) through global partnerships to investigate wetland analyses at multiple scales. The present study investigates the complexity of an inland freshwater wetland system, presenting a conceptual framework for mapping and monitoring the dynamics of Lake Kolleru (a wetland of international importance, as defined by the Ramsar Convention), utilizing a geospatial platform. Illustrating the pace of land use changes leading to the progressive elimination of the wetland ecosystem of freshwater Lake Kolleru, this study also highlights the impacts of such changes on the socio-economic system. A comprehensive temporal analysis (1977-2007) provided a structural base to schematically analyse the dynamics of biophysical and ecological changes to the wetland by effectively using a spectrum of remote sensing data. The present status and changing trends in ecological dimensions of Lake Kolleru were illustrated, utilizing information from spatial analyses, complimented with socio-economic assessment. Attention is drawn to the potential of utilizing earth resources systems in exploring space-time interactions in freshwater ecosystems heavily modified through aquaculture interventions. Further, the spatial derivatives are meant as reference material for local authorities and decision-makers to rehabilitate the economic livelihood activities to the social community dependent on the lake ecosystem. The disseminated message emphasizes the applicability of geospatial tools to enhance the efficacy of the decision-making process by facilitating regular monitoring of ecosystem dynamics and providing updated information on wetland patterns and uses.